Identification of an Aberrant Transligamentous Branch of the Median Nerve during Carpal Tunnel Release using Ultrasound Guidance - Douglas Hoffman, MD; Jay Smith, MD; Katelyn Henningsen, BS (Journal of Hand Surgery Global Online)
Ultrasound is a well-established tool for diagnosing carpal tunnel syndrome and guiding therapeutic release procedures. Variations in carpal tunnel anatomy, including the palmar cutaneous and thenar motor branches, are well-documented. This case describes a novel transligamentous branch of the median nerve, resembling a second palmar cutaneous branch, identified with diagnostic ultrasound prior to an ultrasound-guided carpal tunnel release. Continuous visualization of this aberrant transligamentous branch during the ultrasound-guided carpal tunnel release procedure enabled precise avoidance, reducing the risk of iatrogenic injury.